Veganism and Punk – A Recipe for Resistance: Symbolic Discourse and Meaningful Practice - Sylvestre, Julie (Université d'Ottawa | University of Ottawa, 2009)
This study explores the construction of meaningfulness through an analysis of food – a powerful conveyor of meaning which, in many traditions, serves as an indicator of religiosity and identity. Food can be viewed as a mechanism through which humans define, understand, and experience themselves as authentic individuals; it serves as the interstice where the “sacred” and “profane” can be demarcated, and through which the desires, passions, hopes, and fears of the individual (i.e., the key ingredients to seeking meaning in the world) are expressed. My paper examines the role food plays in the day-to-day lives of Vegan Punks. In particular, it seeks to explore the way food is used ideologically in the creation of distinct beliefs and practices among a community grounded in a sense of ethical righteousness.